Making Sense of Affirmative Action - Lippert-Rasmussen, Kasper (Oxford University Press, Incorporated, 2020)
In this book Kasper Lippert-Rasmussen address the complexities of his question "Is affirmative action morally (un)justifiable?" by analyzing the prevailing contemporary arguments both for and against affirmative action. The book applies current political philosophy to demonstrate that arguments on both sides justify different conclusions given different specific cases, though it ultimately does argue in favor of affirmative action based on the relative strength and significance of the anti-discrimination- and equality of opportunity-based positions